Are therapists aware of the needs of people with disabilities? - M. Petrick; S. Homer; R. Evans (AOSIS, 1999)
This article challenges therapists to find out what the needs of people with disability are before planning community based rehabilitation services. It also establishes that therapists and people with disabilities have different ideas about the needs of people with disability.